2010
DOI: 10.2139/ssrn.1368273
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance and Capital Structure Dynamics

Abstract: We develop a dynamic tradeoff model to examine the importance of managershareholder conflicts in capital structure choice. In the model, firms face taxation, refinancing costs, and liquidation costs. Managers own a fraction of the firms' equity, capture part of the free cash flow to equity as private benefits, and have control over financing decisions. Using data on leverage choices and the model's predictions for different statistical moments of leverage, we find that agency costs of 1.5% of equity value on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
146
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(166 citation statements)
references
References 44 publications
12
146
0
8
Order By: Relevance
“…Anderson et al (2004) found that board independence is negatively related with the cost of debts. Morellec et al (2012) also showed that there is a negative correlation between board independence and agency cost.…”
Section: Outsidersmentioning
confidence: 94%
See 1 more Smart Citation
“…Anderson et al (2004) found that board independence is negatively related with the cost of debts. Morellec et al (2012) also showed that there is a negative correlation between board independence and agency cost.…”
Section: Outsidersmentioning
confidence: 94%
“…It has been pointed out that if one has many outsiders on the board, monitoring would be stricter (Weisbach 1988;Wen et al 2002;Morellec et al 2012). This is interpreted through considering (Jensen 1986) that such outsiders stay away from performance burden itself-since connected with responsibility.…”
Section: Outsidersmentioning
confidence: 99%
“…This results in lower leverage to avoid the performance pressures linked with commitments to pay back large amounts of cash (Jensen, 1986). Morellec et al (2012) asserted that board independence is negatively related to agency costs, since more independent directors provide stronger monitor of management. On the other hand, Pfeffer and Salancick (1978) found that a high proportion of outside directors is associated with high leverage supporting the idea that independent directors help firms to raise more debt through the reduction of information asymmetry, the enhancement of a firm's status and the recognition and exploitation of all available resources.…”
Section: Introduction©mentioning
confidence: 99%
“…The first, which is the main focus of our paper, is represented by differences in production technologies that determine how invested capital translates into cash flows. A second source is the presence of financing frictions that determine the choice between internal and external financing, the capital structure mix, and the allocation of the cash flows among the firm's security holders (Glover, 2011, andMorellec, Nikolov, andSchurhoff, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Notable exceptions that account for heterogeneity in firm parameters are the papers by Morellec, Nikolov, and Schurhoff (2012), who use Simulated Maximum Likelihood to 3 Notice that estimates of investment policy obtained by plant level data are not necessarily representative of the parameters characterizing total corporate investment, since the latter involves a degree of aggregation within firm. 4 The aggregate effects capital adjustment costs have also been the focus of recent macroeconomic models (e.g., Khan and Thomas, 2008).…”
Section: Introductionmentioning
confidence: 99%